On the taxonomy of Afrotropical Coleophoridae (VII). New species of genus Coleophora Hübner, 1822 from Central, Southern Africa and Oman (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio (Zootaxa, 2022)
This work presents the description of 6 new species of the genus Coleophora Hübner from Zimbabwe, Uganda, Ethiopia, Angola, Kenya, and Oman: Coleophora nyangae, sp. nov.,Coleophora kibalensis, sp. nov., Coleophora arcana, sp. nov., Coleophora angolana, sp. nov., Coleophora kinangopensis, sp. nov., Coleophora fracta, sp. nov.